To Work or Not to Work Remotely? Work-to-family Interface Before and During the COVID-19 Pandemic - Ghislieri, Chiara; Molino, Monica; Dolce, Valentina (La Medicina del Lavoro, 2023)
Background: This paper provides a brief, evidence-based reflection on the differences between 'old-normal' remote working and mandatory work-from-home during the Covid-19 pandemic. From the perspective of applied psychology in the field of work and organizations, we used self-report instruments to assess variations in work-family conflict and enrichment, frequency of information and communication technologies use, and recovery in two longitudinal studies. Methods: The first study involved 148 individuals from the technical-administrative staff of a large Italian University, during an experimentation of remote working (one day per week) in 2019. The second study, conducted during the first lockdown in 2020, involved 144 individuals (occasional sample, heterogeneous by profession). All participants completed a self-report online questionnaire two times six months apart. Results: Although the two studies are not directly comparable, the results showed two different situations: in the condition of experimental remote working (one day per week), participants reported a decrease in work-family conflict and an improvement in recovery experiences, while in the emergency remote working condition, a deterioration in work-family enrichment was found. Conclusions: These findings highlighted that some differences exist between a planned remote working condition and a mandatory one in an emergency. We briefly discuss these aspects to inform future organizational decisions and actions for the 'new normal'.